Fluid power maintenance basics and troubleshooting - Mitchell, Richard J. 1919- (Fluid power and control, 1997)
Offers comprehensive coverage of hydraulic system troubleshooting. This book furnishes a fresh paradigm for troubleshooting methodology. It covers typical circuitry found in industrial, agricultural, construction, transportation, utilities maintenance, and fire-fighting equipment as well as heavy presses.